Preparation and characterization of proton exchange membrane (PEM) using polystyrene precursors / Anis Nurdhiani Rosdi - Anis Nurdhiani, Rosdi (2015)
In the present dissertation, proton exchange membrane (PEM) was prepared by using virgin polystyrene and polymeric waste precursors. The adopted sulfonation followed an open and reflux conditions in the presence of dichloroethane and chloroform respectively. Thus the obtained sulfonated polystyrene (SPS) were utilized for the membrane casting using suitable solvents. Concentrated sulfuric acid and freshly prepared acetyl sulfate was employed as sulfonating agent for open and reflux methods respectively. The membrane casting was carried out with and without isolating the sulfonated polystyrene. The zeolite was chosen as an inorganic additive. The synthesized membranes were characterized with Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) to identify the -SO3H functional group attached onto the polymer membrane, thermal stability and surface morphology. The membranes were further examined for their water uptake capacity, swelling behavior and degree of sulfonation. In addition, the crucial performance of the fabricated PEM was scrutinized by experimenting ion exchange capacity (IEC) and proton conductivity analysis. The performed FTIR analysis elucidated the presence of sulfonic and other functional groups in the prepared samples. Further analysis of the degree of sulfonation confirmed the level of sulfonation achieved. The membranes fabricated through an open sulfonation (OS) route exhibited greater swelling characteristics than that of the other samples. The sulfonation via reflux condition using chloroform without zeolite (RCC) and with the inclusion of zeolite (RCC-Z) equivalently displayed good thermal and surface properties. The inclusion of zeolite reduced the water uptake that lead to a less swelling and greater mechanical stability than the one prepared without zeolite. The membranes casted in similar reflux condition but using waste polystyrene as precursor demonstrated good stability towards hydrated condition. The ion exchange capacity of RCC and RCC-Z was found to be 0.030 meq/g and 0.170 meq/g, where else the one obtained using waste PS with varied acetyl sulfonate volume (1 mL and 5 mL) displayed value of 0.220 and 0.536 meq/g respectively. The proton conductivity of the membrane surged by the inclusion of the zeolite (1.11 × 10-5 S/cm), meanwhile the proton conductivity of membrane fabricated through the waste PS with varied acetyl sulfonate volume (1 mL and 5 mL) exhibited an value of 2.03 × 10-6 S/cm and 6.07 × 10-6 S/cm respectively. The present study disclosed the prospective of waste polymers and its obtained inherent properties endorsed its feasibility towards preparation of PEM that outfits fuel cell applications.